2009
DOI: 10.1016/j.fsi.2009.01.004
|View full text |Cite
|
Sign up to set email alerts
|

F-type lectin from the sea bass (Dicentrarchus labrax): Purification, cDNA cloning, tissue expression and localization, and opsonic activity

Abstract: Recently described biochemical and structural aspects of fucose-binding lectins from the European eel (Anguilla anguilla) and striped bass (Morone saxatilis) led to the identification of a novel lectin family ("F-type" lectins) characterized by a unique sequence motif and a characteristic structural fold. The F-type fold is shared not only with other members of this lectin family, but also with apparently unrelated proteins ranging from prokaryotes to vertebrates. Here we describe the purification, biochemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
50
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 33 publications
3
50
0
Order By: Relevance
“…20 The multiple duplicate tandem homologues present in modern teleost orders appear to be the product of independent duplications. 20 Previously, we reported the purification of sea bass (DlFBL) and gilt head bream (SauFBL) serum fucose-binding lectins, 23,30,31 and we also demonstrated that SauFBL displays epitopes recognized by anti-DlFBL-specific antibodies. Furthermore, based on the DlFBL cDNA sequence, we showed that it is a bona fide FTL, as it shares carbohydrate specificity and biochemical properties with other well-characterized FTLs.…”
mentioning
confidence: 89%
See 4 more Smart Citations
“…20 The multiple duplicate tandem homologues present in modern teleost orders appear to be the product of independent duplications. 20 Previously, we reported the purification of sea bass (DlFBL) and gilt head bream (SauFBL) serum fucose-binding lectins, 23,30,31 and we also demonstrated that SauFBL displays epitopes recognized by anti-DlFBL-specific antibodies. Furthermore, based on the DlFBL cDNA sequence, we showed that it is a bona fide FTL, as it shares carbohydrate specificity and biochemical properties with other well-characterized FTLs.…”
mentioning
confidence: 89%
“…Furthermore, based on the DlFBL cDNA sequence, we showed that it is a bona fide FTL, as it shares carbohydrate specificity and biochemical properties with other well-characterized FTLs. 23 FTLs have also been described in the shark To protect the rights of the author(s) and publisher we inform you that this PDF is an uncorrected proof for internal business use only by the author(s), editor(s), reviewer(s), Elsevier and typesetter TNQ Books and Journals Pvt Ltd. It is not allowed to publish this proof online or in print.…”
Section: Fish Ftls: Biochemical and Molecular Featuresmentioning
confidence: 99%
See 3 more Smart Citations